Extensive nasopharyngeal angiofibroma case report (Bangladesh Journal of Otorhinolaryngology, 2010)
Juvenile nasopharyngeal angiofibroma is a benign vascular neoplasm, but it is locally aggressive. This accounts for less than 0.5% of all the neoplasm in the head & neck region in the male population only. Here we report a case of 10-year-old boy with a blackish red smooth polypoidal mass in the nasal cavity, with history of recurrent epistaxis. On physical examination it was suspected as nasopharyngeal angiofibroma. We removed it totally by lateral rhinotomy approach. And the diagnosis was nasopharyngeal angiofibroma on histopathology. Key words: Angiofibroma; Nasopharyngeal. DOI: 10.3329/bjo.v15i2.5061 Bangladesh J Otorhinolaryngol 2009; 15(2): 75-77